Influence of food source on growth of earthworm Amynthas rodericensis (Grube, 1879) under experimental culture - Nguyễn, Văn Thuận; Hoàng, Hữu Tình; Nguyễn , Duy Thuận; Trần , Văn Giang; Trần , Quốc Dung (Hue University Journal of Science: Natural Science, 2022)
Amynthas rodericensis is a common earthworm species in Vietnam. The feeding material and substrate affect the growth and reproduction of earthworms. The individual size, total number, weight, and gain weight of earthworms under laboratory conditions were investigated. The experiment was designed with four treatments (100% pig manure; 75% pig manure and 25% substrate; 50% pig manure and 50% substrate; 25% pig manure and 75% substrate) with six replicates in a completely randomized design; the experiments lasted ten weeks. The maximum growth and reproduction of A. rodericensis are observed with 75% pig manure and 25% substrate.